Therapeutic Potential and Safety of the Cinnamomum zeylanicum Methanolic Extract Against Chronic Toxoplasma gondii Infection in Mice - Alanazi, Abdullah D.; Almohammed, Hamdan I. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: This experimental study aimed to determine the in vitro, in vivo, and toxicity effects of Cinnamomum zeylanicum methanolic extract (CZME) against Toxoplasma gondii infection. Methods: The in vitro activity of CZME T. gondii tachyzoites was studied by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Infected mice were treated with CZME for two weeks at doses of 20, 40, and 60 mg/kg/day. Then, the therapeutic effects of CZME were evaluated by assessing the mean number and the mean size of T. gondii tissue cysts, oxidant-antioxidant enzymes, pro-inflammatory cytokines, and mRNA expression levels of bradyzoite surface antigen 1(BAG1) by real-time PCR. Results: CZME significantly (p<0.001) increased the mortality rate of parasites in a dose- and time-dependent response. The mean number of intracellular tachyzoites was significantly reduced after CZME therapy. Treatment of infected mice with CZME resulted in significant (p<0.001) downregulation of BAG1 and the level of lipid peroxidation (LPO) and nitric oxide (NO) as the oxidative stress markers. However, a considerable rise (p<0.05) was found in the level of antioxidant markers such as glutathione peroxidase (GPx), catalase enzyme (CAT), and superoxide dismutase enzyme activity (SOD). After treatment of infected mice with CZME, the level of pro-inflammatory cytokines of IFN-γ, IL-1β, and IL-12 was considerably elevated in a dose-dependent response. CZME had no significant cytotoxicity on Vero cells with the 50% cytotoxic concentrations of 169.5±5.66 μg/mL. Conclusion: The findings confirmed the promising therapeutic effects of CZME on chronic toxoplasmosis in mice; nevertheless, further investigations are required to confirm these results, elucidate its precise mechanisms, and examine its effectiveness in human volunteers.